Current state of research on acupuncture for the treatment of amyotrophic lateral sclerosis: A scoping review - Siyang Peng; Yukun Tian; Weiqian Chang; Yajing Yang; Shaohong Li; Jinxia Ni; Wenzeng Zhu (Frontiers in Neurology, 2022)
ObjectiveTo provide an overview of the range and characteristics of existing evidence, research gaps, and future research priorities in treating amyotrophic lateral sclerosis (ALS) with acupuncture.MethodClinical studies on acupuncture treatment for ALS were searched in 9 databases and two websites. Two independent researchers screened the literature according to the inclusion and exclusion criteria; extracted the demographic data, interventions, and significant findings of the studies; and comprehensively analyzed the characteristics and limitations of the included articles.ResultsA total of 2,326 studies were retrieved, of which 92 were included. Most of the studies were conducted in China, with the number increasing over time. Study designs included case reports, case series, randomized controlled trials (RCTs), and before-and-after studies, among which case reports were the most frequently used. A total of 1,388 patients were enrolled, of whom 1,031 had ALS, 274 had progressive bulbar palsy (PBP), 60 had progressive muscle atrophy (PMA), and 23 had primary lateral sclerosis (PLS). Acupuncture interventions included body acupuncture, electroacupuncture, acupoint injection, scalp acupuncture, acupoint massage, Sa-am acupuncture, needle-embedding therapy, auricular acupuncture, venom pharmacopuncture therapy, plum blossom needling, acupoint paste, electroacupuncture, and needle warming through moxibustion. The most frequently used acupoints were ST36, LI4, SP6, and LI11. Acupuncture is often applied in combination with other treatments, such as herbal or Western medicine. The frequency of treatment ranged from once a month to three times a day, and the duration of treatment ranged from 5 days to 3 years. Clinical symptoms, muscle strength, and effective rates were the most frequently used outcomes. Most studies reported significant efficacy, and only a few studies reported adverse events explicitly.ConclusionEvidence gaps include poor study design, complex interventions, limited significance of the selected outcomes, and limited study reporting. The promotion of acupuncture treatment for ALS still faces several obstacles. Rigorous study design and conduct, standardized intervention and outcome measurements, and normative reporting are needed to investigate the efficacy and safety of acupuncture treatment for ALS.